A lithium ion battery

By forming a specific nuclear shell structure and fluorine distribution on the surface of the lithium -ion battery, the surface of the negative electrode material of the lithium ion battery can solve the problem of elevated impedance of the SEI membrane and improve the dynamic performance and cycle stability of the battery.

CN116683016BActive Publication Date: 2025-01-28CALB GROUP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310896138.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-28
Estimated Expiration
2043-07-20

AI Technical Summary

Technical Problem

During the surface formation process of existing lithium-ion batteries, the SEI film impedance of the silicon oxygen negative electrode material increases, affecting the kinetic performance and cycle life.

Method used

By forming the first shell, second shell layer, and third shell layer of the surface of the negative electrode material of silicon oxygen particles, the content and distribution of fluorine elements are adjusted, so that the fluorine content in the third shell layer is higher than that of the first shell In the layer, the fluorine content in the first shell layer is higher than that of the second shell layer, and the second shell layer does not contain fluorine.

Benefits of technology

Reduce the impedance of SEI membrane on the surface of silicon oxygen, and improve the dynamic performance and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116683016B_ABST
    Figure CN116683016B_ABST
Patent Text Reader

Abstract

The present application specifically discloses a lithium-ion battery, including a positive electrode, a separator, a negative electrode and an electrolyte; the negative electrode contains silicon oxide particles of a core-shell structure, the silicon oxide particles have a first shell layer, a second shell layer and a third shell layer from the core surface to the position away from the core surface, the fluorine content in the third shell layer is higher than the fluorine content in the first shell layer, and the fluorine content in the first shell layer is higher than the fluorine content in the second shell layer; wherein, the silicon oxide particles from the core surface to the 3rd to 15th nm away from the core surface are the first shell layer, the silicon oxide particles from the core surface to the 15th to 100th nm away from the core surface are the second shell layer, and the silicon oxide particles from the core surface to the 100th to 200th nm away from the core surface are the third shell layer. The present application has the advantages of reducing the SEI film impedance on the surface of silicon oxide negative electrode materials, improving the stability of the SEI film and thus improving the cycle performance of lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a lithium ion battery. Background Art

[0002] Formation refers to the first charging process of a lithium battery after it is filled with electrolyte. This process can activate the active substances in the battery and activate the lithium battery. At the same time, the lithium salt reacts with the additives in the electrolyte to form a solid electrolyte interface (SEI) film on the negative electrode side of the lithium battery. The SEI film can prevent side reactions from occurring, thereby reducing the loss of active lithium in the lithium battery.

[0003] At present, the commonly used negative electrode materials in lithium batteries are graphite negative electrode, silicon oxygen negative electrode and silicon carbon negative electrode; among them, the raw materials of silicon oxygen negative electrode are mainly composed of silicon material and graphite. Silicon oxygen negative electrode is widely used in lithium battery manufacturing because its specific capacity is 10 times that of graphite negative electrode. In addition, FEC is currently a frequently used additive in lithium-ion battery electrolyte and is added in a relatively high amount. This is because FEC can generate a thin and highly stable SEI film on the surface of the negative electrode, which can effectively reduce Li + In addition, reduction occurs during the later cycle of the battery to repair the new interface produced by the particle breakage caused by the breathing expansion of silicon oxygen, thereby improving the cycle life of the lithium-ion battery.

[0004] However, in the actual surface formation process, from the DQ / DV curve after silicon-oxygen negative electrode formation and the GC test of the electrolyte composition, it can be seen that: graphite basically completes the reduction of electrolyte additives before 3V, but when silicon-oxygen is not alloyed with lithium (3.3V), even if the lithium insertion potential of the additive is reached, no obvious additive reduction phenomenon occurs. This is mainly because, before silicon-oxygen is alloyed, the electronic conductivity of the silicon-oxygen surface is poor, and it cannot be electrochemically reduced on the surface of the silicon-oxygen negative electrode; after silicon-oxygen is alloyed with lithium, its surface has the ability to reduce, but at the lithium insertion alloying voltage (3.3V), the additives and solvents in the electrolyte are both reducing. In this process, the priority of the reduction reaction mainly depends on the concentration of each type of additive. It has been mentioned in the above description that when different types of additives are added to the electrolyte, the content of FEC accounts for the highest proportion, which will cause the reduction shell formed at the silicon-oxygen interface to be reduced by FEC, and there is fluorine in the reduction shell formed at the silicon-oxygen interface. Summary of the invention

[0005] In order to improve the performance of a lithium-ion battery, the present application provides a lithium-ion battery.

[0006] The present application provides a lithium-ion battery, which adopts the following technical solution:

[0007] A lithium-ion battery, comprising a positive electrode, a separator, a negative electrode and an electrolyte, wherein the negative electrode contains silicon oxide particles with a core-shell structure, the silicon oxide particles having a first shell layer, a second shell layer and a third shell layer from the core surface to a position away from the core surface, the fluorine content in the third shell layer is higher than the fluorine content in the first shell layer, and the fluorine content in the first shell layer is higher than the fluorine content in the second shell layer;

[0008] Among them, the range of the silicon oxide particles from the core surface to the 3rd to 15th nm away from the core surface is the first shell layer, the range of the silicon oxide particles from the core surface to the 15th to 100th nm away from the core surface is the second shell layer, and the range of the silicon oxide particles from the core surface to the 100th to 200th nm away from the core surface is the third shell layer.

[0009] The presence of fluorine in the reduction shell on the surface of the negative electrode silicon oxide particles can improve the stability of the SEI film on the negative electrode surface, thereby improving the long-term life of the battery. However, the applicant has found that the content and distribution of fluorine will affect the impedance and kinetic performance of the battery. When the reduction shell on the surface of the silicon oxide particles contains fluorine and the content of fluorine is distributed uniformly everywhere, the impedance of the SEI film on the surface of the silicon oxide negative electrode material will be increased, which will have a negative impact on the kinetic performance of the battery.

[0010] The present application forms the above-mentioned first shell layer, second shell layer and third shell layer on the surface of the silicon oxide particle negative electrode material. Compared with the prior art in which the fluorine element is distributed at various depths in the shell layer, the impedance of the SEI film on the surface of the silicon oxide negative electrode material can be reduced, thereby alleviating the negative impact of the increase in the impedance of the SEI film on the kinetic performance of the lithium ion battery; in addition, the core-shell structure of the present invention is compared with the structure in the prior art in which the fluorine element is distributed at various depths in the shell layer, and can further improve the stability of the SEI film on the surface of the silicon oxide negative electrode material, thereby improving the cycle stability of the lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 It is a cross-sectional view of a silicon oxide particle and its surface shell.

[0012] Description of reference numerals:

[0013] 1. The core of the silicon-oxygen particle; 2. The first shell; 3. The second shell; 4. The third shell. DETAILED DESCRIPTION

[0014] For better understanding and implementation, the technical solution of the present invention will be clearly and completely described below in conjunction with embodiments.

[0015] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0016] Unless otherwise indicated, all numerical values ​​expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as modified by the term “about.” Accordingly, unless indicated to the contrary, the numerical parameters set forth herein are approximations that can vary depending upon the desired properties desired to be obtained.

[0017] As used herein, "and / or" means one or all of the mentioned elements.

[0018] As used herein, “including” and “comprising” encompasses the case where only the stated elements are present as well as the case where there are other elements other than the stated elements.

[0019] All percentages in the present invention are by weight, unless otherwise specified.

[0020] Unless otherwise indicated, "a", "an", "an" and "the" used in this specification are intended to include "at least one" or "one or more". For example, "a component" means one or more components, so more than one component may be considered and may be employed or used in the implementation of the embodiment.

[0021] The battery of the present invention comprises a positive electrode, a separator, a negative electrode and an electrolyte; the negative electrode contains silicon oxide particles of a core-shell structure, the silicon oxide particles have a first shell layer, a second shell layer and a third shell layer from the core surface to the position away from the core surface, the fluorine content in the third shell layer is higher than the fluorine content in the first shell layer, and the fluorine content in the first shell layer is higher than the fluorine content in the second shell layer; wherein the silicon oxide particles are in a range of 3 to 15 nm from the core surface to the position away from the core surface as the first shell layer, the silicon oxide particles are in a range of 15 (not including 15) to 100 nm from the core surface to the position away from the core surface as the second shell layer, and the silicon oxide particles are in a range of 100 (not including 100) to 200 nm from the core surface to the position away from the core surface as the third shell layer.

[0022] The range limitation on the first shell layer, the second shell layer and the third shell layer in the present application does not simply limit the thickness of the first shell layer to 12 nm, the thickness of the second shell layer to 85 nm and the thickness of the third shell layer to 100 nm, but means that within the above corresponding ranges of the first shell layer, the second shell layer and the third shell layer, the effect of the fluorine content satisfying the third shell layer>first shell layer>second shell layer is more significant.

[0023] The arrangement of the first shell layer, the second shell layer and the third shell layer in the present application can provide sufficient strength guarantee for the SEI film, thereby alleviating the damage of the shell structure caused by the expansion of silicon and oxygen during the cycle, and thus the stability of the shell; and making the internal resistance of the entire shell layer at a lower level, thereby improving the electrochemical performance of the battery.

[0024] Preferably, the second shell layer does not contain fluorine element.

[0025] If all regions of the silicon oxide particles contain fluorine, the impedance of the SEI film will increase, thereby affecting the dynamic performance of the battery. Therefore, the content of fluorine in the shell layer needs to be reduced; if the outermost side of the shell layer does not contain fluorine, the stability of the SEI film is poor and it is easily dissolved by the electrolyte; if the innermost side of the shell layer does not contain fluorine, the toughness of the SEI film deteriorates, and as the battery is charged and discharged, the SEI film ruptures, and the thickness of the SEI film increases, thereby affecting the cycle performance of the battery. The present application sets the second shell layer to be free of fluorine, which can ensure the toughness and stability of the SEI film without affecting the impedance of the SEI film and the dynamic performance of the battery.

[0026] Preferably, the electrolyte contains FEC and an additive having a reduction potential higher than that of FEC, and the content of FEC is higher than the content of the additive having a reduction potential higher than that of FEC.

[0027] Preferably, the FEC accounts for 3% to 20% of the total mass of the electrolyte.

[0028] Preferably, the additive having a reduction potential higher than that of FEC accounts for 0.5% to 6% of the total mass of the electrolyte.

[0029] Preferably, the FEC accounts for 15% of the total mass of the electrolyte, and the additive having a reduction potential higher than the reduction potential of FEC accounts for 3% of the total mass of the electrolyte.

[0030] By controlling the FEC content to be greater than the content of the additive having a reduction potential higher than the FEC reduction potential, even if part of the FEC is consumed in the first shell during the formation process, due to the high total FEC content, the remaining FEC content in the electrolyte after the first shell is formed can still be greater than the content of the additive having a reduction potential higher than the FEC reduction potential; at the same time, the formation of the second shell consumes a large amount of the additive having a reduction potential higher than the FEC reduction potential, but does not consume FEC, so that when the third shell is subsequently formed, the fluorine content in the third shell can be maintained at a high level, thereby generating a SEI film structure with low impedance and good stability on the surface of the silicon-oxygen negative electrode material, thereby improving the kinetic performance of the lithium-ion battery.

[0031] Preferably, the additive having a reduction potential higher than the FEC reduction potential is selected from at least one of a film-forming additive, a safety additive, a multifunctional additive, and an overcharge protection additive.

[0032] Preferably, the additive having a reduction potential higher than that of FEC is selected from at least one of lithium difluorooxalatoborate, vinyl sulfate, 1,3-propane sultone, propene sultone, and vinylene carbonate.

[0033] First, the combination of lithium difluorooxalatoborate and vinyl sulfate with FEC can significantly improve the cycle performance of lithium-ion batteries. Lithium difluorooxalatoborate has good solubility in carbonate solvents, can provide lithium-ion batteries with higher specific capacity and better low-temperature cycle performance, and can effectively form an SEI film on the graphite surface of the negative electrode; secondly, the reduction potential of the additive vinyl sulfate can be coordinated with the reduction potential of FEC, so that more FEC can be retained in the electrolyte after formation, improving the repair effect of FEC on the broken silicon oxide particles, thereby improving the cycle performance of lithium-ion batteries; finally, the SEI film formed by vinyl sulfate has low impedance, so that the battery has excellent kinetic performance and storage performance.

[0034] Preferably, when there is more than one type of additive whose reduction potential is higher than the FEC reduction potential, the second shell layer is a multi-layer structure; the reduction potential of the additive forming the multi-layer structure in which the second shell layer is close to the first shell layer is lower than the reduction potential of the additive forming the multi-layer structure in which the second shell layer is far from the first shell layer.

[0035] By adopting the above technical scheme, the additive with a reduction potential higher than the FEC reduction potential can form a second shell as much as possible on the surface of the silicon oxide particles during the formation process, and the presence of the additive with a reduction potential higher than the FEC reduction potential is reduced to have a negative impact on the FEC repair silicon oxide negative electrode material during the subsequent lithium ion battery cycle, thereby improving the cycle performance of the lithium ion battery.

[0036] Preferably, the negative electrode further comprises at least one of natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon and soft carbon.

[0037] Preferably, the silicon oxide particles are selected from silicon monoxide and / or a mixture of silicon and carbon.

[0038] The surface of the mixture of silicon and carbon will be oxidized in the air to form an oxide film, thereby introducing silicon oxide particles; and the introduction of silicon oxide particles to obtain a silicon oxide type negative electrode, the reduction potential of the silicon oxide negative electrode is lower than the reduction potential of FEC, after the first shell and the second shell are formed on the surface of the silicon oxide particles, there is still a large amount of unconsumed FEC in the electrolyte, under the action of concentration competition, the FEC in the electrolyte is reduced and forms a third shell, and finally the silicon oxide negative electrode material with a core-shell structure containing the present application is obtained, thereby improving the kinetic performance of the lithium battery.

[0039] Preferably, the formation of the lithium ion battery adopts the following steps:

[0040] (1) charging a lithium-ion battery at 1C-3C to a silicon-oxygen lithium alloying voltage (e.g., greater than or equal to 3.4V), controlling the lithium-ion battery to stay at the silicon-oxygen lithium alloying voltage for 10-60s to obtain a lithium-ion battery after silicon-oxygen alloying treatment; discharging the lithium-ion battery after silicon-oxygen alloying treatment at 1C-3C to a low voltage (e.g., less than or equal to 2.5V), generating a first shell layer on the surface of the silicon-oxygen particles;

[0041] (2) The lithium-ion battery in (1) is charged at 0.1C-0.6C to a high voltage (for example, greater than or equal to 3.8V), and a second shell layer and a third shell layer are sequentially generated on the surface of the silicon oxide particles.

[0042] The first shell begins to form when the battery is charged at a high rate to a high voltage. The reason is that at this time, the silicon of the negative electrode is alloyed when the high voltage is reached, so that it can conduct electrons, and FEC and additives with a reduction potential higher than the FEC reduction potential can be reduced on the negative electrode surface; in the process of high-rate discharge to low voltage, since the reduction potential of FEC and additives with a reduction potential higher than the FEC reduction potential has not yet been reached, the first shell can still be formed in the early stage of high-rate discharge, until the voltage at which FEC and additives with a reduction potential higher than the FEC reduction potential cannot be reduced, at which time the first shell is formed. When the charging operation is continued at a low rate, since additives with a reduction potential higher than the FEC reduction potential are easier to be reduced than FEC, once charged to the corresponding voltage, additives with a reduction potential higher than the FEC reduction potential can be reduced to the negative electrode surface to form the second shell; when the voltage is continued to be increased, since the content of additives with a reduction potential higher than the FEC reduction potential is less, when the FEC reduction potential is reached, the additives with a reduction potential higher than the FEC reduction potential are basically exhausted, and only FEC is reduced to the negative electrode surface and forms the third shell.

[0043] The silicon-oxygen negative electrode material is alloyed to obtain the ability of electronic conductivity. After the silicon-oxygen negative electrode material obtains the ability of electronic conductivity, the charge and discharge voltage is adjusted, so that in the process of forming the first shell layer and the second shell layer on the surface of the silicon-oxygen particles, a large amount of additives with a reduction potential higher than the FEC reduction potential in the electrolyte are consumed, rather than FEC with a higher content, so that FEC can be retained in the electrolyte to the greatest extent, so that FEC can play a role in the later cycle charge and discharge process of the battery, repair the new interface produced by the particle breakage caused by the breathing expansion of the silicon-oxygen particles, improve the stability of the SEI film, and then improve the cycle performance of the battery.

[0044] Example

[0045] Example 1

[0046] 1. Preparation of positive electrode

[0047] The positive electrode slurry was prepared as follows: the positive electrode active material LiNi 6 Co 2 Mn 2 O 2 , conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, solvent NMP is added to the mixed slurry, and the mixture is stirred under the action of a vacuum stirrer until the system is uniform, thereby obtaining a positive electrode slurry;

[0048] The positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a LiNi 6 Co 2 Mn 2 O 2 Positive electrode sheet of active material.

[0049] 2. Preparation of negative electrode

[0050] The negative electrode slurry is prepared as follows: a mixture of artificial graphite and silica particles, conductive carbon black Super-P, a binder styrene-butadiene rubber SBR, and carboxymethyl cellulose CMC are mixed in a mass ratio of 94:1:2.5:2.5, wherein the silica particles account for 7% of the total mass of the mixture, and then the mixed slurry is dispersed in deionized water, and the mixed slurry is stirred until it is uniform under the action of a vacuum mixer to obtain a negative electrode slurry.

[0051] The negative electrode slurry is continuously coated on the negative electrode foil, and the edges of the negative electrode foil are left without coating the slurry on the upper and lower sides of the negative electrode foil. Then, the negative electrode foil at the edge is cut off, leaving a certain width of negative electrode foil as a pole ear.

[0052] 3. Preparation of Electrolyte

[0053] Vinyl carbonate EC, ethyl methyl carbonate EMC, and diethyl carbonate DEC were mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF 6 The electrolyte is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L; then, 0.6% of the total mass of the electrolyte is lithium difluorooxalatoborate LiODFB, 3% of the total mass of the electrolyte is vinyl sulfate DTD, and 15% of the total mass of the electrolyte is fluoroethylene carbonate FEC.

[0054] 4. Selection of isolation film

[0055] In this embodiment, a polyethylene film is selected as the separator of the lithium-ion battery.

[0056] 5. Assembly of lithium-ion batteries

[0057] The preparation method of the lithium-ion battery is as follows: the multi-electrode positive and negative electrode sheets prepared by the above method are wound together with the separator, and the positive and negative electrode ears of the wound winding core are overlapped respectively by setting the distance between the electrode ears. Finally, the winding core is welded to the pole column, and a multi-electrode lithium-ion battery is made after packaging.

[0058] The above lithium-ion battery is formed according to the following steps to obtain a lithium-ion battery subjected to formation treatment:

[0059] (1) charging the lithium-ion battery at 1C to a silicon-oxygen lithium alloying voltage of 3.4V, controlling the lithium-ion battery to stay at the silicon-oxygen lithium alloying voltage for 30s to obtain a lithium-ion battery treated with silicon-oxygen alloying; discharging the lithium-ion battery treated with silicon-oxygen alloying at 1C to a low voltage of 2.5V to generate a first shell layer on the surface of the silicon-oxygen particles;

[0060] (2) The lithium-ion battery in (1) is charged at 0.33C to a high voltage of 3.8V, and a second shell layer and a third shell layer are sequentially generated on the surface of the silicon oxide particles.

[0061] The core-shell structure diagram of the silicon oxide particles prepared in this embodiment is as follows Figure 1 shown.

[0062] Example 2

[0063] This example prepares a lithium-ion battery by referring to the method provided in Example 1. The only difference between this example and Example 1 is that, when the lithium-ion battery is formed, the formation rate of the lithium-ion battery after silicon-oxygen alloying treatment in step (1) is 1.5C; the rest of the parts are the same as Example 1.

[0064] Example 3

[0065] This example prepares a lithium-ion battery by referring to the method provided in Example 1. The only difference between this example and Example 1 is that, when the lithium-ion battery is formed, the formation rate of the lithium-ion battery after silicon-oxygen alloying treatment in step (1) is 2.8C; the rest of the parts are the same as Example 1.

[0066] Example 4

[0067] This example prepares a lithium ion battery by referring to the method provided in Example 1. The only difference between this example and Example 1 is that when the lithium ion battery is formed, the formation rate in step (2) is 0.5C; the rest is the same as Example 1.

[0068] Example 5

[0069] This example prepares a lithium ion battery by referring to the method provided in Example 1. The only difference between this example and Example 1 is that when the lithium ion battery is formed, the formation rate in step (2) is 0.2C; the rest is the same as Example 1.

[0070] Example 6

[0071] This example prepares a lithium ion battery by referring to the method provided in Example 1. The only difference between this example and Example 1 is that when the lithium ion battery is formed, the formation rate in step (2) is 0.55C; the rest is the same as Example 1.

[0072] Example 7

[0073] This example prepares a lithium ion battery by referring to the method provided in Example 1. The only difference between this example and Example 1 is that when the lithium ion battery is formed, the formation rate in step (2) is 0.18C; the rest is the same as Example 1.

[0074] Comparative Example 1

[0075] This comparative example prepares a lithium ion battery by referring to the method provided in Example 1. The only difference between this comparative example and Example 1 is that a common formation method is used in the formation process. In this comparative example, the formation method is: forming at a high temperature of 0.05°C to 3.8V; standing at high temperature for 12h, and constant volume at 0.33°C (2.5-4.35V), to obtain a formed lithium ion battery.

[0076] Since the voltage is directly increased to 3.8V in this formation step, all additives are directly reduced at this voltage and are directly reduced and deposited on the negative electrode surface to form a SEI film, rather than forming different SEI films in layers.

[0077] Comparative Example 2

[0078] This comparative example prepares a lithium ion battery according to the method provided in Example 1. The difference between this comparative example and Example 1 lies in the preparation of the electrolyte and the parameter setting of the formation step;

[0079] The electrolytes used in this embodiment are electrolyte A and electrolyte B;

[0080] Electrolyte A was prepared by the following steps: vinylene carbonate EC, ethyl methyl carbonate EMC, and diethyl carbonate DEC were mixed in a volume ratio of 1:1:1 to obtain an organic solvent; then, fully dried lithium salt LiPF 6 Dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L; then, lithium difluorooxalatoborate LiODFB accounting for 0.6% of the total mass of the electrolyte and vinyl sulfate DTD accounting for 3% of the total mass of the electrolyte were added to the solution to prepare electrolyte A;

[0081] Electrolyte B was prepared by the following steps: vinylene carbonate EC, ethyl methyl carbonate EMC, and diethyl carbonate DEC were mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF 6 Dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L; then, fluoroethylene carbonate FEC accounting for 15% of the total mass of the electrolyte was added to the solution to prepare electrolyte B;

[0082] The formation steps of the lithium battery in this comparative example are:

[0083] (1) After injecting electrolyte A into the lithium-ion battery, charging the lithium-ion battery at 0.33C to a silicon-oxygen lithium alloying voltage of 3.8V, controlling the lithium-ion battery to stay at the silicon-oxygen lithium alloying voltage for 30s, and obtaining a lithium-ion battery treated with silicon-oxygen alloying; discharging the lithium-ion battery treated with silicon-oxygen alloying at 0.33C to a low voltage of 2.4V, and generating a first shell layer on the surface of the silicon-oxygen particles;

[0084] (2) After injecting electrolyte B into the lithium ion battery in (1), charging at 0.33C to a high voltage of 3.8V, a second shell layer and a third shell layer are sequentially generated on the surface of the silicon oxide particles.

[0085] The rest of the parts are consistent with Example 1.

[0086] Comparative Example 3

[0087] This comparative example prepares a lithium ion battery by referring to the method provided in comparative example 2. The difference between this comparative example and comparative example 2 lies in the formation operation of the lithium ion battery; the rest is the same as comparative example 2.

[0088] The formation steps of the lithium battery in this comparative example are:

[0089] (1) After injecting electrolyte B into the lithium-ion battery, charging the lithium-ion battery at 0.22C to a silicon-oxygen lithium alloying voltage of 3.8V, controlling the lithium-ion battery to stay at the silicon-oxygen lithium alloying voltage for 30s, and obtaining a lithium-ion battery after silicon-oxygen alloying treatment; discharging the lithium-ion battery after silicon-oxygen alloying treatment at 0.33C to a low voltage of 2.4V, and generating a first shell layer on the surface of the silicon-oxygen particles;

[0090] (2) After injecting electrolyte A into the lithium ion battery in (1), charging at 0.33C to a high voltage of 3.8V, a second shell layer and a third shell layer are sequentially generated on the surface of the silicon oxide particles.

[0091] The rest of the parts are the same as those in Comparative Example 2.

[0092] Detection Methods

[0093] 1. XPS performance test

[0094] XPS performance test was performed on the negative electrode sheets prepared in Examples 1-7 and Comparative Examples 1-3. The specific measures and steps are as follows: After the constant capacity battery is discharged, the negative electrode sheets are charged at H 2 O<5ppm; O 2 The negative electrode was disassembled in a glove box with a concentration of less than 5ppm. The disassembled negative electrode was dried in the glove box environment and then sealed and sent for XPS testing. The negative electrode was etched with Ar ions, with an etching area of ​​4mm×4mm and an etching rate of 1.3nm / 100s. XPS analysis was performed on the electrode after etching for different times to obtain the content of fluorine in the first shell layer, the second shell layer, and the third shell layer. 2. EIS performance test

[0095] The lithium-ion batteries prepared in Examples 1-7 and Comparative Examples 1-3 were discharged after constant capacity to adjust the state of charge to 50% SOC, and the EIS test was performed on the battery cells. The test conditions were: frequency range of 100 kHz to 0.01 Hz, amplitude of 10 mV; the data after the test were fitted with a circuit to obtain the SEI film impedance, and the test data were recorded in Table 1.

[0096] 3. Cycle performance test

[0097] The lithium ion batteries prepared in Examples 1-7 and Comparative Examples 1-3 were placed in an oven at a constant temperature of 25°C, charged to 4.40V at a constant current of 1C, then the constant voltage charging current was reduced to 0.05C, left to stand for 10 minutes, and then discharged to 2.5V at a constant current of 1C, and cycled in this way until the capacity was less than 80% of the initial capacity (cycle cutoff condition), and the number of cycles at this time was recorded in Table 1.

[0098] Table 1

[0099]

[0100] Combined with Example 1, Comparative Example 1 Table 1 and Figure 1 It can be seen that the first shell layer, the second shell layer and the third shell layer structure formed in Example 1 reduce the impedance of the SEI film generated on the surface of the silicon oxygen negative electrode material relative to the SEI film in Comparative Example 1, and improve the cyclability of the lithium battery in Example 1 relative to the lithium ion battery in the embodiment; this is because the fluorine content in each shell layer in Example 1 satisfies the third shell layer> the first shell layer> the second shell layer, and the fluorine content in the second shell layer is 0, while the fluorine element is uniformly distributed in the shell layer generated on the surface of the silicon oxygen particles in Comparative Example 1. Therefore, the shell layer structure and fluorine element distribution in Example 1 make the SEI film have higher toughness and can resist the expansion of the silicon oxygen negative electrode material during the cycle, and higher stability can reduce its solubility in the electrolyte, thereby improving the stability of the silicon oxygen negative electrode material and improving the cyclability of the lithium ion battery.

[0101] In combination with Example 1, Comparative Examples 2-3 and Table 1, it can be seen that if only the outermost third shell layer is controlled to contain no fluorine element, the stability of the SEI film will be reduced, making it easy to dissolve in the electrolyte; if only the innermost first shell layer is controlled to contain no fluorine element, the inner SEI film on the surface of the negative electrode material has poor toughness, and as the battery is charged and discharged, the SEI film will rupture, thereby increasing the thickness of the SEI film, thereby affecting the cycle performance of the battery; therefore, in order to reduce the content of fluorine element in the overall shell layer, the present invention adopts the middle second shell layer to be set without fluorine element, while the first shell layer close to the surface of the negative electrode material and the third shell layer far from the surface of the negative electrode material contain fluorine element, thereby obtaining a SEI film structure with low impedance and excellent stability on the surface of the silicon oxide particle negative electrode material, thereby improving the stability of the lithium ion battery.

[0102] In combination with Examples 1, 2-7 and Table 1, it can be seen that by adjusting the rate in step (1) or step (2), the cycle performance of the lithium battery is slightly reduced compared with the cycle performance of the lithium battery in Example 1. In particular, when adjusting the rate in step (1), the thickness of the first shell layer will produce a more obvious change, which will slightly reduce the cycle performance of the lithium battery.

[0103] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a separator, a negative electrode and an electrolyte; the negative electrode contains silicon oxide particles with a core-shell structure, the silicon oxide particles have a first shell layer, a second shell layer and a third shell layer from the core surface to the part away from the core surface, the fluorine content in the third shell layer is higher than the fluorine content in the first shell layer, and the fluorine content in the first shell layer is higher than the fluorine content in the second shell layer; The first shell layer is the range of 3 to 15 nm from the core surface of the silicon-oxygen particle to the 15 to 100 nm away from the core surface of the silicon-oxygen particle, and the third shell layer is the range of 100 to 200 nm from the core surface of the silicon-oxygen particle to the 15 to 100 nm away from the core surface of the silicon-oxygen particle. The electrolyte contains FEC and an additive having a reduction potential higher than that of FEC, and the content of FEC is higher than the content of the additive having a reduction potential higher than that of FEC; The additive having a reduction potential higher than that of FEC is selected from at least one of lithium difluorooxalatoborate and vinyl sulfate.

2. A lithium ion battery according to claim 1, characterized in that: The FEC accounts for 3% to 20% of the total mass of the electrolyte.

3. A lithium ion battery according to claim 1, characterized in that: The additive having a reduction potential higher than that of FEC accounts for 0.5% to 6% of the total mass of the electrolyte.

4. A lithium ion battery according to any one of claims 1 to 3, characterized in that: The FEC accounts for 15% of the total mass of the electrolyte, and the additive having a reduction potential higher than that of the FEC accounts for 3% of the total mass of the electrolyte.

5. The lithium-ion battery according to claim 1, characterized in that: When there is more than one type of additive whose reduction potential is higher than that of FEC, the second shell layer is a multilayer structure; the reduction potential of the additive in the multilayer structure forming the second shell layer close to the first shell layer is higher than the reduction potential of the additive in the multilayer structure forming the second shell layer far from the first shell layer.

6. A lithium ion battery according to claim 1, characterized in that: The negative electrode further comprises at least one of natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon and soft carbon.

7. A lithium ion battery according to claim 1, characterized in that: The silicon-oxygen particles are selected from a mixture of silicon monoxide and carbon and / or a mixture of silicon and carbon.

Citation Information

Patent Citations

  • Preparation method of silicon-based soft package lithium ion battery

    CN114865058A